Intensificação de capital e meio ambiente: mudanças no sistema agrícola com irrigação nos cerrados do entorno de Iraí de Minas - Silva, Edileuza Pereira (2000)
Modern agriculture in the cerrados is in the process of transformation. In its trajectory, irrigation has been used as a tool for intensifying production and as a means to overcome the crisis of realization of agrarian capital. This process provides an increase in the productive and monetary yields of agriculture, however, it also leads to the emergence of environmental problems. In this perspective, this work sought to accompany the evolution of agriculture in the cerrados, seeking to identify a development trend manifested from agricultural modernization. The region of the Surrounding of Irai de Minas was taken as a reference, represented by the Pantaninho and Divisa Microbasins, as it presents representative characteristics of the cerrados agroecosystems and is one of the first areas of developmental intervention through PRODECER. The analysis carried out in this work shows that the irrigated system caused a change in the central axis of the accumulation of the production systems of the Pantaninho plateaus, with the replacement of soybean and corn cultivation by higher value products, with emphasis on beans, peas , potatoes, sweet corn and coffee. On the other hand, the environmental effects of this process have been damaging, given the intensification in the use of land and pesticides, water scarcity and generation of conflicts between producers due to this scarcity. In addition, Divisa's producers have been completely marginalized from this process, mainly because they are located in a rugged area and are poor in natural resources and because of their limited access to financial resources.